2017
DOI: 10.1089/dia.2017.0063
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Real-Life Study on the Effect of Flash Glucose Monitoring on Glycemic Control in Patients with Type 1 and Type 2 Diabetes

Abstract: This study shows that FCGM-based AGP with FreeStyle LibrePro is associated with significant reductions in A1c levels in both T1D and T2D. In addition, improvement in A1c levels was maintained across all age groups and in patients enrolled at different diabetes clinics in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…Two studies compared retrospective CGM using flash CGM with visual charts and counseling to SMBGL. Greater HbA1c reductions were observed following CGM after 12 weeks (−0.9 vs −0.7%, P < 0.001) in 4,678 individuals, but not after 24 weeks (−0.28 vs −0.21%, P = 0.822) of 224 individuals taking multiple daily insulin injections. After 12 weeks, HbA1c reduction with retrospective CGM was similar when combined with either problem‐solving counseling or standard diabetes education (no counseling; −0.7 vs −0.5; P = 0.69).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies compared retrospective CGM using flash CGM with visual charts and counseling to SMBGL. Greater HbA1c reductions were observed following CGM after 12 weeks (−0.9 vs −0.7%, P < 0.001) in 4,678 individuals, but not after 24 weeks (−0.28 vs −0.21%, P = 0.822) of 224 individuals taking multiple daily insulin injections. After 12 weeks, HbA1c reduction with retrospective CGM was similar when combined with either problem‐solving counseling or standard diabetes education (no counseling; −0.7 vs −0.5; P = 0.69).…”
Section: Resultsmentioning
confidence: 99%
“…After removal of duplications, and excluding articles based on title and abstracts, 12 articles, reporting 11 separate studies (one article reporting long-term follow up 24 of a previously reported short-term intervention 25 ) met the inclusion criteria. Nine articles (eight studies) were RCTs [24][25][26][27][28][29][30][31][32] , and three were observational trials [33][34][35] . Included studies were rated as being of acceptable quality 19 .…”
Section: Search Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown the accuracy of interstitial glucose measurements, and the usefulness and safety of FGM [5][6][7][8][9][10][11] . Furthermore, it has been shown that the use of FGM reduced hypoglycemia in patients with type 1 and type 2 diabetes mellitus, although the effects of FGM on glycemic control are controversial 7,8,[12][13][14][15] . However, in most of the earlier studies, capillary blood glucose, not venous blood glucose, was used as a reference, and the accuracy of glucose measurements by FGM has not been fully determined 5,6,9,10,16 .…”
Section: Introductionmentioning
confidence: 99%